Sebum, acne, skin elasticity, and gender difference – which is the major influencing factor for facial pores?. Issue 1 (28th December 2011) - Kim, BY; Choi, JW; Park, KC; Youn, SW
<x xml:space="preserve">Abstract</x> Background Enlarged facial pores have been esthetic problems and have become a matter of cosmetic concern. Several factors are supposed to be related to the enlargement of facial pores, although scientific evaluations were not performed yet. Objective To assess the correlation between facial pores and possible relating factors such as age, gender, sebum secretion, skin elasticity, and the presence of acne, using objective bioengineering instruments. Methods Sixty volunteers, 30 males and 30 females, participated in this study. Various parameters of facial pores were assessed using the Robo Skin Analyzer®. The facial sebum secretion and skin elasticity were measured using the Sebumeter® and the Cutometer®, respectively. These data were compared and correlated to examine the possible relationship between facial pores and age, sebum secretion and skin elasticity, according to gender and the presence of acne. Results Male gender and the existence of acne were correlated with higher number of facial pores. Sebum secretion levels showed positive correlation with facial pores. The R7 parameter of skin elasticity was negatively correlated with facial pores, suggesting increased facial pores with decreased skin elasticity. However, the age and the severity of acne did not show a definite relationship with facial pores. Conclusion Male, increased sebum and decreased skin elasticity were mostly correlated with facial pore development. Further studies on population with various demographic profiles and more severe acne may be helpful to elucidate the potential effect of aging and acne severity on facial pores.